C[sbnd]C bond cleavage in the electrooxidation of 2,3-butanediol controlled by an ionic liquid modifier - Yang, Juntao; Haßfurther, Florian; Hilpert, Felix; Hussain, Zarah; Yang, Tian; Taccardi, Nicola; Wasserscheid, Peter; Brummel, Olaf; Libuda, Jörg (Journal of Catalysis, 2024)
In heterogeneous catalysis, ionic liquids (ILs) are used as chemical modifiers to control selectivity. In our work, we aim to apply the same concept to electrocatalytic systems. As a model reaction, we studied the electrooxidation of 2,3-butanediol on the low-index Pt(1 1 1), Pt(1 0 0) and Pt(1 1 0) surfaces in an acidic environment. We used the IL 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ([C2C1Im][OTf]) dissolved in an aqueous electrolyte as a catalyst modifier. The reaction mechanisms were investigated by electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). The oxidation of 2,3-butanediol is highly structure dependent. On all three surfaces, the two products formed are acetoin and diacetyl, i.e. either one or two alcohol functionalities are oxidized. However, we observe distinct features on the different surfaces with respect to activity, potential window of oxidation, and selectivity. Only the Pt(1 0 0) surface is active towards C[sbnd]C bond cleavage. The latter reaction leads to the formation of COads and poisoning of the catalyst. Modification of this surface by addition of the IL leads to an increase of the selectivity for acetoin from 51 % to 78 % (at 1.1 VRHE). In addition, C[sbnd]C bond cleavage is suppressed, no CO is formed, and the surface remains active for the target reaction. We attribute these effects to the reversible and structure dependent adsorption of the [OTf]− anions on the Pt surfaces and additional interionic interactions. Our results demonstrate the potential of ILs to control selectivity in electrocatalytic reactions.
CRIS-Team Scopus Importer:2024-05-31
Keywords: In-situ IR spectroscopy; Ionic liquids; Platinum; Secondary alcohols; Selectivity; Single crystals; Supported catalyst with ionic liquid layer

Heterogeneously Catalyzed Energy Release in Azaborinine-based Molecular Solar Thermal Systems - Hussain, Zarah; Einholz, Ralf; Biebl, Sonja M.; Franz, Evanie; Müller, Adrian; Dreuw, Andreas; Bettinger, Holger F.; Brummel, Olaf; Libuda, Jörg (Topics in Catalysis, 2025)
Molecular solar thermal (MOST) systems combine the conversion, storage and release of solar energy using switchable photoisomers. Isomerization of azaborinines (BN-benzenes) to their Dewar isomers (BN-Dewar) yields BNB/BND couples, representing a relatively new class of MOST systems with promising properties for energy storage. However, so far only homogeneous catalysts are available for triggering energy release, which does not allow for a straightforward catalyst-photoisomer separation. In this work, we investigate the heterogeneously catalyzed energy release of two different BNB/BND-based MOST systems, namely 1-(tert-butyldimethylsilyl)-2-mesityl-1,2-dihydro-1,2-azaborinine/2-(tert-butyldimethylsilyl)-3-mesityl-2-aza-3-borabicyclo[2.2.0]hex-5-ene (BNB1/BND1) and 1-(tert-butyl)-2-mesityl-1,2-dihydro-1,2-azaborinine/2-(tert-butyl)-3-mesityl-2-aza-3-borabicyclo[2.2.0]hex-5-ene (BNB2/BND2), using Au(111) as a potential catalytic material. We used highly oriented pyrolytic graphite (HOPG) as inert reference surface. In our study, we combined photochemical infrared reflection absorption spectroscopy (PC-IRRAS) with density functional theory (DFT). We show that Au(111) is active in releasing the energy stored in a BNB/BND MOST system. However, the catalytic activity is strongly dependent on the substituents. Although the activity of the Au catalyst is too low to be implemented in applications, our study provides proof of principle that a heterogeneously catalyzed approach is applicable.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Azaborine; Catalysis; Gold; In-situ IR spectroscopy; Photoswitches; Solar energy storage

Surface science and liquid phase investigations of oxanorbornadiene/oxaquadricyclane ester derivatives as molecular solar thermal energy storage systems on Pt(111) - Hemauer, Felix; Krappmann, Daniel; Schwaab, Valentin; Hussain, Zarah; Freiberger, Eva Marie; Waleska-Wellnhofer, Natalie; Franz, Evanie; Hampel, Frank; Brummel, Olaf; Libuda, Jörg; Hirsch, Andreas; Steinrück, Hans-Peter; et al. (Journal of Chemical Physics, 2023)
The transition to renewable energy sources comes along with the search for new energy storage solutions. Molecular solar thermal systems directly harvest and store solar energy in a chemical manner. By a suitable molecular design, a higher overall efficiency can be achieved. In this study, we investigate the surface chemistry of oxa-norbornadiene/quadricyclane derivatives on a Pt(111) surface. Specifically, we focus on the energy storage and release properties of molecules that are substituted with ester moieties of different sizes. For our model catalytic approach, synchrotron radiation-based x-ray photoelectron spectroscopy measurements were conducted in ultra-high vacuum (UHV) and correlated with the catalytic behavior in the liquid phase monitored by photochemical infrared reflection absorption spectroscopy. The differences in their spectral appearance enabled us to unambiguously differentiate the energy-lean and energy-rich isomers and decomposition products. Next to qualitative information on the adsorption motifs, temperature-programmed experiments allowed for the observation of thermally induced reactions and the deduction of the related reaction pathways. We analyzed the selectivity of the cycloreversion reaction from the energy-rich quadricyclane derivative to its energy-lean norbornadiene isomer and competing processes, such as desorption and decomposition. For the 2,3-bis(methylester)-substitution, the cycloreversion reaction was found to occur between 310 and 340 K, while the thermal stability limit of the compounds was determined to be 380 K. The larger 2,3-bis(benzylester) derivatives have a lower apparent adsorption energy and a decomposition onset already at 135 K. In the liquid phase (in acetonitrile), we determined the rate constants for the cycloreversion reaction on Pt(111) to k = 5.3 × 10-4 s-1 for the 2,3-bis(methylester)-substitution and k = 6.3 × 10-4 s-1 for the 2,3-bis(benzylester) derivative. The selectivities were of >99% and 98% for the two molecules, respectively. The difference in the catalytic behavior of Pt(111) for both derivatives is less pronounced in the liquid phase than in UHV, which we attribute to the passivation of the Pt(111) surface by carbonaceous species under ambient conditions.
CRIS-Team Scopus Importer:2023-09-01